Complex influence of climate on the distribution and body size of an Alpine species - Baroni D.; Masoero G. (Wiley, 2022)
1.Alpine species with a limited distribution can act as sentinels of climate change, but first we have to identify their climate‐sensitive traits. Here, we adopted a multi‐level approach to define the influence of climate on the geographical distribution and body size of a steno‐endemic Alpine grasshopper, the Stenobothrus ursulae Nadig, 1986.
2.We built a species distribution model (SDM) with the following climatic predictors: precipitation seasonality, precipitation of the wettest month, mean temperature of the driest quarter and isothermality. The model provides a satisfactory representation of the species geographical range, but it also identifies areas suitable in terms of climate in which the species was not found. Therefore, we suggest that climatic and geographic barriers combined with a poor dispersal ability might have limited its distribution.
3.We measured 309 individuals collected across the whole geographical range. Our results show that increasing elevation was linked both to a decline in S. ursulae body length (converse Bergmann's rule) and to a decline in sexual size dimorphism (converse Rensch's rule). We demonstrate also that the same climatic predictors that describe the species distribution affect its morphological variation.
4.Our results suggest that climate affects this species distribution and body size with opposite effects: suitable climatic conditions are found at high elevations, and the fitness‐related trait (i.e. body size) declines with elevations. In the future, distribution and/or morphology of the species might change in order to successfully cope with the changing climate, but its very limited dispersal ability constitutes an issue of concern.